Mitigation of wildlife disturbance at oil and gas industry electrical facilities in Riau Province, Indonesia - SUWONDO SUWONDO; DARMADI DARMADI; DEFRI ROZA; FRI MURDIYA; REBY OKTARIANDA; DODI DWI RISAUNDI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Suwondo, Darmadi, Roza D, Murdiya F, Oktarianda R, Risaundi DD. 2023. Mitigation of wildlife disturbance at oil and gas industry electrical facilities in Riau Province, Indonesia. Biodiversitas 24: 6914-6922. Electrical facilities in the oil and gas industry often experience interference from wildlife, disrupting oil and gas operational activities. Solutions are required to mitigate these disturbances. This research analyzes the level of wildlife disturbance in electrical facilities in the oil and gas industry and their mitigation. This research used a survey method with purposive random sampling; the observation was carried out in the work area of Pertamina Hulu Rokan Company, Riau Province, Indonesia. The data obtained are primary and secondary, and the parameters measured consist of population, behavior, disturbance, and mitigation of disturbance to wildlife. A total of 38 species of wild animals were found, consisting of the mammal group (5 species), the reptile group (3 species), and the aves group (30 species). The population of long-tailed monkey (Macaca fascicularis) is the largest species of mammal found (1,500 individuals), and the most common daily behaviors of macaques are climbing (22.5%), eating (17.5%), and playing (15%). There were 169 incidents of wildlife disturbance at the WK Rokan electrical facility, with the most disturbance caused by macaques at 111 incidents. Disturbance from wildlife has a linear positive interaction with wildlife mortality around oil and gas industry electrical facilities. Mitigation is conducted as follows: isolating/eliminating the presence of wild animals in affected facilities/locations, building barriers against wild animals around electrical facilities, and providing repellents.